Shadow and Bone - Book 1 - Bardugo, Leigh (New York : Henry Holt, 2012)
Orphaned by the Border Wars, Alina Starkov is taken to become the protegé of the mysterious Darkling, who trains her to join the magical elite in the belief that she is the Sun Summoner, who can destroy the monsters of the Fold.
Keywords: Magic -- Fiction; Ability -- Fiction; Monsters -- Fiction; Orphans -- Fiction; Fantasy fiction